Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1136/bjsports-2012-091219
|View full text |Cite
|
Sign up to set email alerts
|

Coding OSICS sports injury diagnoses in epidemiological studies: does the background of the coder matter?

Abstract: ObjectiveTo compare Orchard Sports Injury Classification System (OSICS-10) sports medicine diagnoses assigned by a clinical and non-clinical coder.DesignAssessment of intercoder agreement.SettingCommunity Australian football.Participants1082 standardised injury surveillance records.Main outcome measurementsDirect comparison of the four-character hierarchical OSICS-10 codes assigned by two independent coders (a sports physician and an epidemiologist). Adjudication by a third coder (biomechanist).ResultsThe code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Another factor which may have contributed to the variation in injury incidence is the issue of who made the injury diagnosis. Similar assumptions have been highlighted by Finch et al 77 in their study stating that differences in expertise and knowledge can result in different outcomes of diagnosis. A wide range of personnel, including doctors, nurses, trainers or players self-reporting, were involved in the reporting process among the studies we included in our review.…”
Section: Discussionsupporting
confidence: 76%
“…Another factor which may have contributed to the variation in injury incidence is the issue of who made the injury diagnosis. Similar assumptions have been highlighted by Finch et al 77 in their study stating that differences in expertise and knowledge can result in different outcomes of diagnosis. A wide range of personnel, including doctors, nurses, trainers or players self-reporting, were involved in the reporting process among the studies we included in our review.…”
Section: Discussionsupporting
confidence: 76%
“…Second, the hours of training/competition and injuries registered in this study were reported by players (ie, self‐report data) and were not diagnosed personally by a health professional. However, all injury cases were reviewed by a physiotherapist and coded according to the Orchard Sports Injury Classification System version 10 (OSICS‐10), which has an overall high level of agreement between coders . This does not rule out that having a health professional to evaluate the injured athlete “on the field” may minimize report bias in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with previous studies using the same methods to register injuries in different sports. Clarsen et al 11 reported a mean prevalence of injury of 25% (95% CI [24][25][26][27] in Olympic and Paralympic athletes from team, endurance, and tactical/technical sports followed up in a weekly basis. The mean prevalence of overuse injuries was higher (20% [95% CI [18][19][20][21]) than acute injuries (4% [95% CI 3-5]).…”
Section: Prevalence and Nature Of Injurymentioning
confidence: 99%
“…The diagnosis, mechanism of injury, and time modified due to injury were entered by the athletes’ treating physiotherapist or doctor into the Athlete Management System (AMS) (Fair Play Pty Ltd) and classified using the Orchard Sports Injury Classification System (OSICS) medical diagnoses 30 . All players were diagnosed clinically ± using additional imaging by the state sports physiotherapist (Cricket Australia state physiotherapists require post‐graduate qualifications in sports physiotherapy) and/ or sports doctor (Cricket Australia doctors are required to be either sports physicians, sport physician registrars, or general practitioners with a special interest in sports medicine).…”
Section: Methodsmentioning
confidence: 99%